The Principal’s Leadership Management Strategy in Improving the Performance Quality of Educators and Educational Staff at State Elementary School 09, Bongan District, West Kutai Regency - Kristianto Hari Setiono; Syamsuddin Mallala; Rhini Fatmasari (Journal of General Education and Humanities, 2026)
This study aims to examine in depth the principal’s leadership management strategy in improving the performance quality of educators and educational staff at State Elementary School 09, Bongan District, West Kutai Regency. A qualitative approach with a case study design was employed. The research focuses on the principal’s leadership management functions, including planning, organising, implementing, and supervising, as well as the performance quality of educators and educational staff, viewed from the aspects of work quality, quantity, timeliness, effectiveness, and independence. Data were collected through in-depth interviews, observations, and documentation using purposive sampling involving the principal, teachers, and educational staff. Data analysis was conducted using the interactive model of Miles and Huberman. The findings indicate that the principal’s leadership management strategy has been implemented in a structured manner, although it has not yet been fully optimised. This condition is influenced by less systematic planning, suboptimal task organisation, and limited human resources and facilities. Nevertheless, the performance quality of educators and educational staff shows positive trends, particularly in work quality, effectiveness, and independence. Supporting factors include strengthening the principal’s leadership competence and professional development, while inhibiting factors include limited resources and challenges in communication and coordination.